2014
DOI: 10.1186/2045-5380-4-12
|View full text |Cite
|
Sign up to set email alerts
|

Reduced hippocampal and medial prefrontal gray matter mediate the association between reported childhood maltreatment and trait anxiety in adulthood and predict sensitivity to future life stress

Abstract: BackgroundThe experience of early life stress is a consistently identified risk factor for the development of mood and anxiety disorders. Preclinical research employing animal models of early life stress has made inroads in understanding this association and suggests that the negative sequelae of early life stress may be mediated by developmental disruption of corticolimbic structures supporting stress responsiveness. Work in humans has corroborated this idea, as childhood adversity has been associated with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
3
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 50 publications
3
90
3
7
Order By: Relevance
“…A few recent neuroimaging studies, like the current one, have begun to search for specific brain mediators of the negative psychiatric effects produced by adversity. For example, Gorka et al (60) report that frontomedial and hippocampal cortical volumes mediate the relation between childhood mistreatment and trait anxiety, while Rao et al (61) have shown that hippocampal volume mediates the relation between childhood mistreatment and higher risk of depression in adulthood (61). An advantage of the current study was that the brain areas examined were identified by an independent measure of impulsivity rather than by their direct association with adversity.…”
Section: Discussionmentioning
confidence: 67%
“…A few recent neuroimaging studies, like the current one, have begun to search for specific brain mediators of the negative psychiatric effects produced by adversity. For example, Gorka et al (60) report that frontomedial and hippocampal cortical volumes mediate the relation between childhood mistreatment and trait anxiety, while Rao et al (61) have shown that hippocampal volume mediates the relation between childhood mistreatment and higher risk of depression in adulthood (61). An advantage of the current study was that the brain areas examined were identified by an independent measure of impulsivity rather than by their direct association with adversity.…”
Section: Discussionmentioning
confidence: 67%
“…Given evidence that neural adaptations to caregiving adversity can be anxiolytic (Gee et al, 2013), it was hypothesized that altered amygdala-hippocampal-mPFC function during aversive learning would predict reduced anxiety among PI youth.…”
Section: Significance Statementmentioning
confidence: 99%
“…Converging cross-species evidence suggests that early adversity alters the structure and function of brain regions involved in aversive learning, including the amygdala, hippocampus, and medial prefrontal cortex (mPFC; Mirescu et Spinelli et al, 2009;Tottenham et al, 2010;Uchida et al, 2010;Jackowski et al, 2011;Tottenham et al, 2011;Gee et al, 2013;Malter Cohen et al, 2013;Pagliaccio et al, 2014;McEwen et al, 2016). Although it is known that early adversity alters the neural bases of aversive learning and predicts anxiety in adults ( …”
Section: Introductionmentioning
confidence: 99%
“…Психические травмы ранней жизни оказывают не-благоприятное воздействие на развитие не только гиппо-кампа, но и других отделов нервной системы; в частности, они приводят к поражению кортиколимбических струк-тур, с функциями которых связывают чувствительность к стрессу [31].…”
Section: психологические и биологические аспекты патогенезаunclassified
“…К сказанному выше можно добавить, что проведен-ные на лабораторных животных эксперименты показали, что стрессы раннего возраста могут вызывать и структур-ные изменения серого вещества гиппокампа, миндалины и префронтальной коры большого мозга [31], т.е. структур мозга, которые обеспечивают эмоциональное реагирова-ние, а с двумя последними связано функционирование системы вознаграждения (reward system), механизмов подкрепления (reinforcement) и формирование зависимо-сти от ПАВ.…”
Section: психологические и биологические аспекты патогенезаunclassified